Nanoscale silician defects in magnetite record protolith inheritance and control chain silicate growth during skarn formation - Jing Xu; Yuri Tatiana Campo-Rodriguez; Cristiana L. Ciobanu; Nigel J. Cook; Ashley Slattery; Benjamin P. Wade; Jiaxing Hu; Taiping Zhao (Lithos, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Associations between air pollution and markers of neuroinflammation, synaptic dysfunction and core Alzheimer’s disease pathology vary by APOE genotype - Kana Kimura; Ira Driscoll; Noah Cook; Sonia Shahzad; Tobey J. Betthauser; Sterling C. Johnson; Sanjay Asthana; Catherine L. Gallagher; Bruce P. Hermann; Mark A. Sager; Kaj Blennow; Henrik Zetterberg; et al. (Neurotoxicity Research, 2026)
To determine whether long-term residential air pollution [AP; ozone (O₃) and fine particulate matter (PM₂.₅)] is associated with (1) incident mild cognitive impairment (MCI) or Alzheimer’s disease (AD), (2) biomarkers of core and AD-relevant pathology, and (3) whether these relationships are moderated by APOE4+/- (carrier/non-carrier of one or both ε4 alleles) status or mediated by neuroinflammation. Sample included 795 participants (Mage 68.7 ± 7.9; 68% female) from the Wisconsin Alzheimer’s Disease Research Center and Wisconsin Registry for Alzheimer’s Prevention parent studies, both enriched for AD risk at enrollment based on parental AD history. Residential zip code and 2009–2021 EPA-based annual AP reports were used to estimate individual exposure. Cox proportional hazards models assessed MCI/AD risk. Linear regressions examined the relationships between AP exposure and biomarkers of core and AD-relevant pathology, with and without APOE4 + stratification. Causal mediation analysis examined whether markers of inflammation mediated the AP-AD pathology relationships. Neither O₃ nor PM₂.₅ exposure predicted MCI/AD incidence nor core AD pathology (Ps > 0.05). Higher PM₂.₅ was associated with higher CSF GFAP levels ( P = 0.003). APOE4 + with higher levels of PM₂.₅ exposure had higher CSF levels of tTau ( P = 0.01), pTau₁₈₁ ( P = 0.01) and neurogranin ( P = 0.02). These relationships were not mediated by neuroinflammation (Ps > 0.05). In this AD-risk enriched cohort, AP was not associated with MCI/AD incidence. However, higher PM₂.₅ exposure was associated with astrocytic activation, and in APOE4+, AD pathology, neurodegeneration, and synaptic dysfunction. Our findings suggest AP as an environmental risk factor contributing to AD-relevant pathology, particularly among genetically at-risk individuals.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Associations of endocrine disrupting chemical biomarkers and their mixture with vitamin D biomarker concentrations in childhood: The HOME Study - Katherine M. Marquess; Jordan R. Kuiper; Taylor M. Etzel; Bruce P. Lanphear; Andrew N. Hoofnagle; Antonia M. Calafat; Julianne Cook Botelho; Maria Ospina; Andreas Sjodin; Lesliam Quirós-Alcalá; Kim M. Cecil; Aimin Chen; et al. (Environmental Research, 2026)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

What temperature is best for the offshore farming of the Australasian snapper, Chrysophrys auratus ? A collective examination of growth, FCR, O 2 consumption and welfare - Selwyn P. Collins; Leonardo J. Magnoni; Denham G. Cook; Suzanne E. Black; Neill A. Herbert (New Zealand Journal of Marine and Freshwater Research, 2025)
The Australasian snapper ( Chrysophrys auratus ) is a candidate for offshore aquaculture in New Zealand. The culture of snapper requires knowledge of the best locations for farms and a key variable is water temperature. The oxygen‐ and capacity‐limited thermal tolerance (OCLTT) hypothesis suggests fish performance is optimised at the temperature that maximises absolute aerobic scope (AAS), whereas the ‘multiple performances–multiple optima’ (MPMO) idea, suggests AAS and other performance measures can have different optimal temperatures. Therefore, the applicability of the OCLTT for snapper was tested by holding juveniles at 15, 18, 21, or 24°C for two months and constructing thermal performance curves (TPCs) for specific growth rate (SGR), feed conversion ratio (FCR) and AAS, and an assessment of welfare indicators. We hypothesised that the OCLTT would apply with all TPCs optimised at 21°C. However, AAS showed no discernible peak with temperature (although lower at 15 than 18°C); SGR and FCR improved non‐linearly with temperature; and welfare indicators varied little with temperature. This lack of aerobic limitation and evidence of MPMO suggests snapper are amenable to culture across a significant temperature range with warmer water likely providing the highest levels of productivity with maintained welfare.

Predicting the yield of Pinus taeda (L.) using UAV LiDAR data in random forest and support vector machine models - Gunjan Barua; David R. Carter; Valerie A. Thomas; P. Corey Green; Phil Radtke; Thomas J. Pingel; Rachel L. Cook; Timothy J. Albaugh; Rafael Rubilar; Otavio Campoe; Matthew Sumnall (Forest Ecology and Management, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Forty-five years of removal campaigns for feral ungulates reveal strategies for success and future directions - Nathan P. Snow; Keely J. Kohen; Ingrid A. Messer; Abigail Pagels; Seth M. Cook; Scott Beckerman; Travis Guerrant; Kurt C. VerCauteren; Kim M. Pepin (Biological Invasions, 2025)
Feral or invasive ungulates (hereafter: feral ungulates) exist worldwide, and their ability to thrive threatens biodiversity, degrades ecosystems, and causes damage to agriculture and properties. Strategies for removing feral ungulates from their introduced insular and mainland ranges have varied greatly, successes have been difficult, and the need is increasing. We reviewed published scientific literature on feral ungulate eradication and maximum control campaigns during 1978–2023 to identify practices that led to greater success. Of 54 campaigns, 32 (59%) reported success. Most campaigns focused on feral swine (61%; Sus scrofa ) or feral goats (24%; Capra hircus ). The average duration of a campaign was 61 months and cost an average of $1.9 m ($USD 2024) or $636/km 2 /month. The most important components for success included ensuring adequate funding was secured for the campaign ($0.5–1 million/km 2 is recommended) and population recovery or reinvasion were minimized. The frequency of campaigns has increased during the last 45 years; however, the areas worked (km 2 ), monthly durations, removal techniques used, funding, and ultimately the rates of success have not changed. A lack of increasing success for larger and more complex campaigns indicated that modernization of technologies for population control has been minimal, and larger breakthroughs are needed. Safe and effective toxicants and sterilants may provide those advances if developed. Lessons learned from campaigns indicate that pilot testing control methods prior to initiating full campaigns may help to alleviate uncertainties, produce more reliable plans, and help inform the biology of the animals being targeted for removal.

MLH1 c.27G>A (p.Arg9=) is a synonymous likely/pathogenic variant underlying variably mosaic constitutional MLH1 methylation in Lynch syndrome - Rocio Alvarez; Paula Climent-Cantó; GiWon Shin; Francesca Paola Aguirre; Lisa Zhou; Dennis J. Hazelett; Brent K. Larson; Covadonga Vara; Gabriel Capellá; Víctor Lorca Castellanos; Pilar Garre Rubio; Françoise Desseigne; et al. (Familial Cancer, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Past and present bacterial communities in deglaciating northern latitude catchments reveal varied soil carbon sequestration potential - Saule Akhmetkaliyeva; Andrew P. Dean; Leon J. Clarke; Simon J. Cook; Sharon Ruiz Lopez; Robert B. Sparkes (Science of The Total Environment, 2025)

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Comparing efficiencies of population control methods for responding to introductions of transboundary animal diseases in wild pigs - Nathan P. Snow; Benjamin Smith; Michael J. Lavelle; Michael P. Glow; Kayleigh Chalkowski; Bruce R. Leland; Sarah Sherburne; Justin W. Fischer; Keely J. Kohen; Seth M. Cook; Hatton Smith; Kurt C. VerCauteren; et al. (Preventive Veterinary Medicine, 2024)

Avoidance and attraction responses of kittiwakes to three offshore wind farms in the North Sea - Christopher J. Pollock; Daniel T. Johnston; Philipp H. Boersch-Supan; Chris B. Thaxter; Elizabeth M. Humphreys; Nina J. O’Hanlon; Gary D. Clewley; Ewan D. Weston; Judy Shamoun-Baranes; Aonghais S. C. P. Cook (Marine Biology, 2024)
Seabird collision risk is a key concern in relation to the environmental impacts associated with offshore wind farms (OWFs). Understanding how species respond both to the wind farm itself, and individual turbines within the wind farm, is key to enabling better quantification and management of collision risk. Collision risk is of particular concern for the black-legged kittiwake, Rissa tridactyla , where modelling predicts unsustainable population level impacts. In this study 20 adult breeding kittiwakes, were tracked with GPS from Whinnyfold, Scotland (57°23′07″N, 001°52′11″W) during the breeding season in 2021. An Avoidance-Attraction Index (AAI) was estimated at several bands within macro- and meso-scales (0–4 km from outer boundary and 0–400 m from turbines, respectively), and the Avoidance Rate (AR; used in environmental impact assessments) at macro-scale to estimate avoidance behaviour to three operational OWFs within their foraging range. One offshore wind farm and its buffer zone (0–4 km from outer boundary) was visited more frequently by the majority of tracked individuals (19/20 birds), despite being twice as far as the closest OWF (17.3 and 31.9 km respectively), whilst 10 or less individuals used the remaining two OWFs. At the most frequented OWF we found macro-scale attraction to the closest band (0–1 km) trending towards avoidance in the furthest band (3–4 km). At the meso-scale we found avoidance of areas below the rotor height range (RHR, a.k.a. rotor swept area/zone) up to 120 m from individual turbines, which decreased to 60 m when within the RHR. Our results indicate that kittiwakes may be slightly attracted to the area around OWFs or aggregate here due to displacement but avoid individual turbines. Increased productivity in the OWF area may potentially be drawing birds into the general area, with aversion to individual turbines being responsible for meso-scale observations.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Influence of wind on kittiwake Rissa tridactyla flight and offshore wind turbine collision risk - Jacob G. Davies; Philipp H. Boersch-Supan; Gary D. Clewley; Elizabeth M. Humphreys; Nina J. O’Hanlon; Judy Shamoun-Baranes; Chris B. Thaxter; Ewan Weston; Aonghais S. C. P. Cook (Marine Biology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

Redefining timing, genesis and geodynamic setting of polymetallic skarn mineralization, Gangdese belt, Tibet, from LA–ICP–MS garnet U–Pb geochronology - Jing Xu; Jiadai Li; Nigel J. Cook; Cristiana L. Ciobanu; Shitou Wu; Benjamin P. Wade; Taiping Zhao; Liyuan Wang (Gondwana Research, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

A framework for studying the effects of offshore wind energy development on birds and bats in the Eastern United States - Kathryn A. Williams; Julia Gulka; Aonghais S. C. P. Cook; Robert H. Diehl; Andrew Farnsworth; Holly Goyert; Cris Hein; Pamela Loring; David Mizrahi; Ib Krag Petersen; Trevor Peterson; Kate McClellan Press; et al. (Frontiers in Marine Science, 2024)
Offshore wind energy development (OWED), while a key strategy for reducing carbon emissions, has potential negative effects to wildlife that should be examined to inform decision making and adaptive management as the industry expands. We present a conceptual framework to guide the long-term study of potential effects to birds and bats from OWED. This framework includes a focus on exposure and vulnerability as key determinants of risk. For birds and bats that are exposed to OWED, there are three main effects of interest that may impact survival and productivity: 1) collision mortality, 2) behavioral responses, including avoidance, displacement, and attraction, and 3) habitat-mediated effects to prey populations. If these OWED effects cause changes in survival and/or breeding success (e.g., fitness), they have the potential for population-level consequences, including changes in population size and structure. Understanding the influence of ecological drivers on exposure and effect parameters can help to disentangle the potential impacts of OWED from other stressors. We use this theoretical framework to summarize existing relevant knowledge and identify current priority research questions (n=22) for the eastern United States, where large-scale development of OWED is primarily in the planning and early construction phase. We also identify recommendations for study design and further prioritization of research topics.

What is known, unknown, and needed to be known about damage caused by wild pigs - Kurt C. VerCauteren; Kim M. Pepin; Seth M. Cook; Sophie McKee; Abigail Pagels; Keely J. Kohen; Ingrid A. Messer; Michael P. Glow; Nathan P. Snow (Biological Invasions, 2024)
Damage assessments provide evidence for initiating and evaluating management programs that protect natural resources and human livelihoods against invasive species. Wild pigs ( Sus scrofa ) cause extensive damage in their native and non-native ranges, but the extent of current damage and efficacy of management of the damage (i.e., population control of wild pigs, exclusion fencing, etc.) remains poorly described. We conducted a systematic review of physical damage caused by wild pigs to summarize what is known and identify knowledge gaps for damage assessment. Wild pig damage assessments have been overwhelmingly qualitative (84% of studies) and measured differently across studies, which prevents the determination of typical damage amounts to a particular resource and comparison across studies. Key priorities going forward are to standardize damage assessments quantitatively and measure population density (or index of such) of wild pigs concurrently with damage assessments to determine the relationship between damage and population levels. We provide a framework for inferring damage in new areas and assessing the benefits of management—to evaluate and optimize landscape-scale management programs. Overall, we recommend future studies strive for: (1) report the amount of damages in a standardized fashion (e.g., area damaged/area surveyed), (2) evaluate and report the amount of damage relative to the density of wild pigs, and (3) when reporting economic costs of damages incurred and management actions, describe the economic valuation method used along with the year of reference for the valuation. Capturing these elements are necessary steps to predict the benefits of management for an area with particular profile of resources and wild pig density, even in areas where damage assessments are not available. Meeting these criteria with allow for more generalizable results that can inform managers across the nearly global distribution of wild pigs.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Spatial variation in spawning timing for multi-species Acropora assemblages in the Red Sea - Eslam O. Osman; David J. Suggett; Tamer M. Attalla; Marco Casartelli; Nathan Cook; Islam El-Sadek; Ahmed Gallab; Elizabeth A. Goergen; Neus Garcias-Bonet; Jessica S. Glanz; Pedro Henrique Pereira; Megan Ramirez-Sanchez; et al. (Frontiers in Marine Science, 2024)
Sexual reproduction is a crucial process for reef building coral populations to maximize genetic diversity and recover from large scale disturbances. Mass spawning events by Acropora species represent critical opportunities for populations to persist, and a process that is increasingly exploited to actively restore degraded reefs. However, the timing and predictive capacity of coral spawning throughout the broad thermal and environmental regime of the Red Sea – a region also undergoing significant development and active reef restoration – remains patchy. We, therefore, conducted three parallel reef surveys in the central Red Sea (Al-Fahal Reef, Thuwal - Saudi Arabia) and the eastern (Shushah Island - Saudi Arabia) and western (Hurghada – Egypt) coast of the northern Red Sea. Surveys assessed the gravidity of gonads, spawning timing, alignment with the lunar cycle of 21 Acropora spp. (total n= 572 colonies) around the full moons of April and May 2023. Consistent with past observations, synchronous spawning was observed for Acropora spp. in both the central and northern Red Sea during April and May, respectively. Interestingly, corals spawned on the full moon in both Shushah and Thuwal sites. In contrast, corals in Hurghada were independent of the lunar cycle and spawned 7-9 nights before the full moon in May. By integrating our 2023 observations with the historical spawning events in Hurghada and Thuwal (2002-2022), we found that the deviation of spawning timing from the full moon day was correlated with absolute Sea Surface Temperature (SST) (earlier spawning before the full moon day, lower SST) and warming rate (earlier spawning, more rapid warming) in 6-weeks prior to spawning. As such, temperature pattern is likely one of the primary factors governing gamete release, among other factors, that likely influence spawning day within the lunar month. These correlations between SST metrics and spawning timing suggest a potential framework to predict future Acropora spp. spawning dates. Our observations demonstrate the importance of parallel efforts across borders to collect critical data needed to inform management strategies aimed at conserving and restoring coral reefs in this ecologically diverse region.

Spontaneous Behavioural Recovery Following Stroke Relates to the Integrity of Parietal and Temporal Regions - Joseph Y. Nashed; Kaden T. Shearer; Justin Z. Wang; Yining Chen; Elise E. Cook; Allen A. Champagne; Nicole S. Coverdale; Juan Fernandez-Ruiz; Shirley I. Striver; J. Randal Flanagan; Jason P. Gallivan; Douglas J. Cook (Translational Stroke Research, 2024)

Behavioural responses of Sandwich terns following the construction of offshore wind farms - Chris B. Thaxter; Ros M. W. Green; Mark P. Collier; Rachel C. Taylor; Robert P. Middelveld; Emily S. Scragg; Lucy J. Wright; Aonghais S. C. P. Cook; Ruben C. Fijn (Marine Biology, 2024)

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - M. Bluett-Duncan; D. Astill; R. Charbak; J. Clayton-Smith; S. Cole; P.A. Cook; J. Cozens; K. Keely; J. Morris; R. Mukherjee; E. Murphy; P. Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Total thermal neutron cross section measurements of hydrogen dense polymers from 0.0005–20 eV - D. Fritz; Y. Danon; K. Ramic; C.W. Chapman; J.M. Brown; G. Arbanas; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; P. Brain; A. Ney; et al. (Annals of Nuclear Energy, 2023)

Imaging geomechanical properties of shales with infrared light - Jungin Lee; Olivia J. Cook; Andrea P. Argüelles; Yashar Mehmani (Fuel, 2023)

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

Total thermal neutron cross section measurements of yttrium hydride from 0.0005 - 3 eV - D. Fritz; Y. Danon; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; C.W. Chapman; G. Arbanas; J.M. Brown; K. Ramic; X. Hu; S. Singh; et al. (Annals of Nuclear Energy, 2023)

Effect of biosecurity practices and diseases on growth and carrageenan properties of Kappaphycus alvarezii and Eucheuma denticulatum cultivated in Zanzibar, Tanzania - Msafiri A. Ndawala; Flower E. Msuya; Jennefe P. Cabarubias; Cicilia S. B. Kambey; Amelia S. Buriyo; Esther F. Mvungi; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2022)

Skarn-style alteration in Proterozoic metasedimentary protoliths hosting IOCG mineralization: the Island Dam Prospect, South Australia - William Keyser; Cristiana L. Ciobanu; Kathy Ehrig; Marija Dmitrijeva; Benjamin P. Wade; Liam Courtney-Davies; Max Verdugo-Ihl; Nigel J. Cook (Mineralium Deposita, 2022)
New mineralogical, geochemical, and geochronological data are presented for the Island Dam prospect, Olympic Cu-Au Province, South Australia. Skarn assemblages comprising actinolite/phlogopite + K-feldspar + magnetite suggest the presence of calcareous protoliths at Island Dam and indicate high-temperature alkali-calcic alteration in the early stages of IOCG mineralization, as seen in other deposits in the region. Dating of lamellar hematite intergrown with Cu-Fe-sulfides allows the timing of the alteration-mineralization event to be constrained at 1594 ± 28 Ma, contemporaneous with the ~ 1.59 Ga IOCG mineralization event recorded across the eastern Gawler Craton. The host metasedimentary sequence can be correlated to the Wallaroo Group based on lithology and fabrics, and stratigraphically by an underlying ~ 1850 Ma Donington Suite granite and the new U–Pb ages for superimposed mineralization. Oscillatory zoned silician magnetite in skarn displays a trace element signature comparable to that observed in the outer shell of the Olympic Dam deposit and the nearby Wirrda Well prospect and is consistent with early stages of IOCG mineralization. The geochemical signatures of hematite from skarn and banded Fe-rich metasedimentary rocks share a common enrichment in W, Sn, Mo, Th, and U seen in hematite from IOCG-style mineralization across the Gawler Craton. Relative enrichment in As, Sb, Ni, and Co is, however, specific to iron-oxides from banded Fe-rich metasedimentary rocks. These features can be attributed to pre-existing iron-rich lithologies.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Evolution of a hydrothermal ore-forming system recorded by sulfide mineral chemistry: a case study from the Plaka Pb–Zn–Ag Deposit, Lavrion, Greece - Max Frenzel; Panagiotis Voudouris; Nigel J. Cook; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin P. Wade (Mineralium Deposita, 2022)
Laser ablation-inductively coupled plasma-mass spectrometry and electron-probe microanalysis were used to investigate the trace-element contents of sphalerite, chalcopyrite and pyrite from the Plaka Pb–Zn–Ag deposit. Using petrographic observations, the analytical results could be linked to the temporal evolution of the Plaka ore-forming system. Sphalerite chemistry reliably records the temperature and f S 2 evolution of the system, with estimated formation temperatures reproducing the microthermometric results from previous fluid-inclusion studies. Chalcopyrite chemistry also shows systematic variations over time, particularly for Cd, Co, Ge, In, Sn and Zn concentrations. Measurable pyrite was only found in association with early high-temperature mineralisation, and no clear trends could therefore be identified. We note, however, that As and Se contents in pyrite are consistent with formation temperatures estimated from co-existing sphalerite. Statistical analysis of the sphalerite data allowed us to identify the dominant geological controls on its trace-element content. The three investigated factors temperature, f S 2 , and sample location account for > 80% of the observed variance in Mn, Fe, Co, Ga, Ge, In, Sb and Hg concentrations, and > 60% of the observed variance in Cd and Sn concentrations. Only for Cu and Ag concentrations is the explained variance < 50%. A similarly detailed analysis was not possible for chalcopyrite and pyrite. Nevertheless, comparison of the results for all three investigated minerals indicates that there are some systematic variations across the deposit which may be explained by local differences in fluid composition.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Small artificial waterbodies are widespread and persistent emitters of methane and carbon dioxide - M. Peacock; J. Audet; D. Bastviken; S. Cook; C. D. Evans; A. Grinham; M. A. Holgerson; L. Högbom; A. E. Pickard; P. Zieliński; M. N. Futter (Global Change Biology, 2021)
Inland waters play an active role in the global carbon cycle and emit large volumes of the greenhouse gases (GHGs), methane (CH 4 ) and carbon dioxide (CO 2 ). A considerable body of research has improved emissions estimates from lakes, reservoirs and rivers but recent attention has been drawn to the importance of small, artificial waterbodies as poorly quantified but potentially important emission hotspots. Of particular interest are emissions from drainage ditches and constructed ponds. These waterbody types are prevalent in many landscapes and their cumulative surface areas can be substantial. Furthermore, GHG emissions from constructed waterbodies are anthropogenic in origin and form part of national emissions reporting, whereas emissions from natural waterbodies do not (according to Intergovernmental Panel on Climate Change guidelines). Here, we present GHG data from two complementary studies covering a range of land uses. In the first, we measured emissions from nine ponds and seven ditches over a full year. Annual emissions varied considerably: 0.1–44.3 g CH 4 m −2 year −1 and −36–4421 g CO 2 m −2 year −1 . In the second, we measured GHG concentrations in 96 ponds and 64 ditches across seven countries, covering subtropical, temperate and sub‐arctic biomes. When CH 4 emissions were converted to CO 2 equivalents, 93% of waterbodies were GHG sources. In both studies, GHGs were positively related to nutrient status (C, N, P), and pond GHG concentrations were highest in smallest waterbodies. Ditch and pond emissions were larger per unit area when compared to equivalent natural systems (streams, natural ponds). We show that GHG emissions from natural systems should not be used as proxies for those from artificial waterbodies, and that artificial waterbodies have the potential to make a substantial but largely unquantified contribution to emissions from the Agriculture, Forestry and Other Land Use sector, and the global carbon cycle.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Corrigendum to: The global Microcystis interactome - K.V. Cook; C. Li; H. Cai; L.R. Krumholz; K.D. Hambright; H.W. Paerl; M.M. Steffen; A.E. Wilson; M.A. Burford; H.‐P. Grossart; D. P. Hamilton; H. Jiang; et al. (Limnology and Oceanography, 2021)

Understanding biosecurity: knowledge, attitudes and practices of seaweed farmers in the Philippines - Jonalyn P. Mateo; Iona Campbell; Elizabeth J. Cottier-Cook; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Anicia Q. Hurtado (Journal of Applied Phycology, 2021)
Farmers are one of the most important components of any plant-based cultivation industry. The Philippines is one of the world’s major producers of red carrageenophyte algae and has tens of thousands of farmers involved in this industry. The production of algae such as Kappaphycus and Eucheuma increased significantly from the early 1970s, when the industry was established, before declining from the mid-2000s, due to a number of reasons, including disease and epiphyte outbreaks. The introduction of biosecurity measures has been one approach used to tackle this decline. Biosecurity-related knowledge, attitude and practices (KAP) of the seaweed farmers were assessed in the four highest seaweed producing regions in the Philippines: (1) Tawi-Tawi, (2) Palawan, (3) Zamboanga and (4) Bohol. Analyses showed that seaweed farmers from Tawi-Tawi had relatively higher KAP mean scores than the other three sites. Palawan and Bohol farmers, however, scored lower on their knowledge, higher on their attitude and highest on their practices compared with the other areas. Farmers from Zamboanga scored the lowest in both their attitude and practice mean scores, although their knowledge score was one of the highest. This is the first KAP assessment applied to the seaweed farming industry globally and the results, in which the farmers’ biosecurity-related knowledge and practices, which scored “Fair” (50–75%) across all the regions, and their attitudes, which scored predominantly “Good” (> 75%) suggest that there is potential to raise the score for biosecurity practices. This assessment highlights how biosecurity challenges are currently addressed by seaweed farmers in the Philippines and suggests how the KAP survey could be used as a tool by policymakers and scientists to address gaps in biosecurity management practices.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Antibiotics modulate biofilm formation in fish pathogenic isolates of atypical Aeromonas salmonicida - Andrew P. Desbois; Kira J. Cook; Elizabeth Buba (Journal of Fish Diseases, 2020)
Atypical Aeromonas salmonicida causes furunculosis infections of non‐salmonid fish, which requires antibiotic therapy. However, antibiotics may induce biofilm in some bacteria, which protects them against hostile conditions while allowing them to persist on surfaces, thus forming a reservoir for infection. The aim of this study was to determine whether atypical isolates of A. salmonicida increased biofilm in the presence of two antibiotics, florfenicol and oxytetracycline. A microtitre plate assay was used to quantify biofilm in the presence and absence of each antibiotic. Fifteen of 28 isolates formed biofilms under control conditions, while 23 of 28 isolates increased biofilm formation in the presence of at least one concentration of at least one antibiotic. For oxytetracycline, the most effective concentration causing biofilm to increase was one‐quarter of that preventing visible bacterial growth, whereas for florfenicol it was one‐half of this value. This is the first study to demonstrate that a bacterial pathogen of fish increases biofilm in response to antibiotics. Biofilm formation may increase the risk of re‐infection in culture systems and this lifestyle favours the transmission of genetic material, which has implications for the dissemination of antibiotic‐resistance genes and demonstrates the need for enhanced disease prevention measures against atypical A. salmonicida .

Biosecurity policy and legislation for the global seaweed aquaculture industry - Iona Campbell; Cicilia S. B. Kambey; Jonalyn P. Mateo; Sadock B. Rusekwa; Anicia Q. Hurtado; Flower E. Msuya; Grant D. Stentiford; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Each year a significant proportion of global food production is lost to pests and diseases, with concerted efforts by government and industry focussed on application of effective biosecurity policies which attempt to minimise their emergence and spread. In aquaculture the volume of seaweeds produced is second only to farmed fish and red algal carrageenophytes currently represent approximately 42% of global production of all seaweeds. Despite this importance, expansion of the seaweed sector is increasingly limited by the high prevalence of recalcitrant diseases and epiphytic pests with potential to emerge and with the demonstrated propensity to spread, particularly in the absence of effective national and international biosecurity policies. Developing biosecurity policy and legislation to manage biosecurity risk in seaweed aquaculture is urgently required to limit these impacts. To understand current international biosecurity frameworks and their efficacy, existing legislative frameworks were analysed quantitatively for the content of biosecurity measures, applicability to the seaweed industry, and inclusion of risks posed by diseases, pests and non-native species. Deficiencies in existing frameworks included the following: inconsistent terminology for inclusion of cultivated seaweeds, unclear designation of implementation responsibility, insufficient evidence-based information and limited alignment of biosecurity hazards and risks. Given the global importance of the cultivation of various seaweeds in alleviating poverty in low and middle income countries, it is crucial that the relatively low-unit value of the industry (i.e. as compared with other aquatic animal sectors) should not conflate with a perceived low risk of disease or pest transfer, nor the subsequent economic and environmental impact that disease transfer may impact on receiving nations (well beyond their seaweed operations). Developing a clear basis for development of robust international biosecurity policies related to the trade in seaweeds arising from the global aquaculture industry, by first addressing the gaps highlighted in this study, will be crucial in limiting impacts of pests and diseases on this valuable industry and on natural capital in locations where seaweeds are farmed.

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Analysis of biosecurity-related policies governing the seaweed industry of the Philippines - Jonalyn P. Mateo; Iona Campbell; Elizabeth J. Cottier-Cook; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Anicia Q. Hurtado (Journal of Applied Phycology, 2020)

Numerical modelling of rare earth element fractionation trends in garnet: a tool to monitor skarn evolution - Jing Xu; Cristiana L. Ciobanu; Nigel J. Cook; Youye Zheng; Xiaofeng Li; Benjamin P. Wade; Max R. Verdugo-Ihl; Wenyuan Gao; Qiaoqiao Zhu (Contributions to Mineralogy and Petrology, 2020)

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Tree-ring reconstructions of cool season temperature for far southeastern Australia, 1731–2007 - K. J. Allen; K. J. Anchukaitis; M. G. Grose; G. Lee; E. R. Cook; J. S. Risbey; T. J. O’Kane; D. Monselesan; A. O’Grady; S. Larsen; P. J. Baker (Climate Dynamics, 2019)

The Influence of Human Demography on Land Cover Change in the Great Lakes States, USA - Mark J. Ducey; Kenneth M. Johnson; Ethan P. Belair; Barbara D. Cook (Environmental Management, 2018)

Delayed timing of successful spawning of an estuarine dependent fish, black bream Acanthopagrus butcheri - Gregory P. Jenkins; Julia A. Kent; Ryan J. Woodland; Fiona Warry; Stephen E. Swearer; Perran L. M. Cook (Journal of Fish Biology, 2018)
In this paper, we investigate the period of successful spawning for black bream Acanthopagrus butcheri , an obligate estuarine species in southern Australia that typically spawn in spring and early summer. However, back‐calculated spawning dates of juveniles sampled in Gippsland Lakes, Victoria from February to May 2016 indicated that spawning was concentrated over a short period in the Austral mid‐summer (January), with a second spawning in late summer and early autumn (late February–early March). Ichthyoplankton sampling in the tributary estuaries from October to early December collected substantial numbers of fish larvae, dominated by gobiids, eleotrids and retropinnids of freshwater origin, but no A. butcheri . The lack of A. butcheri larvae was consistent with the delayed successful spawning indicated by juvenile otolith data. Freshwater flows declined from late winter to summer, with consistent salinity stratification of the water column. Dissolved oxygen (DO) concentrations were generally very low below the halocline. These conditions may have delayed the upstream spawning migration of adults or may have been unsuitable for survival of eggs and newly‐hatched larvae. Longer‐term predictions for climate change in southern Victoria, including the Gippsland Lakes region, are for lower winter–spring freshwater flows, potentially benefiting the reproductive success of A. butcheri through high water‐column stratification, but only if DO concentrations are not compromised by a lack of high winter flows needed to flush low DO water from the system.

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Applying the principles of isotope analysis in plant and animal ecology to forensic science in the Americas - Lesley A. Chesson; Janet E. Barnette; Gabriel J. Bowen; J. Renée Brooks; John F. Casale; Thure E. Cerling; Craig S. Cook; Charles B. Douthitt; John D. Howa; Janet M. Hurley; Helen W. Kreuzer; Michael J. Lott; et al. (Oecologia, 2018)

The role of catchment land use and tidal exchange in structuring estuarine fish assemblages - F. Y. Warry; P. Reich; P. L. M. Cook; R. Mac Nally; R. J. Woodland (Hydrobiologia, 2018)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Development and characterization of a synthetic infectious cDNA clone of the virulent Bucyrus strain of equine arteritis virus expressing mCherry (red fluorescent protein) - Shankar P. Mondal; R. Frank Cook; R. Lakshman Chelvarajan; Pamela J. Henney; Peter J. Timoney; Udeni B. R. Balasuriya (Archives of Virology, 2016)

Nitrogen loads explain primary productivity in estuaries at the ecosystem scale - Ryan J. Woodland; James R. Thomson; Ralph Mac Nally; Paul Reich; Victor Evrard; Fiona Y. Wary; Jeffrey P. Walker; Perran L. M. Cook (Limnology and Oceanography, 2015)
Increased nutrient loads stimulate estuary primary productivity and can alter the structure and function of biological communities within estuaries, particularly when producer groups respond differently to changes in nutrient availability. Here, the relative influence of riverine inputs of nitrogen and phosphorus were compared to determine their contribution to estuarine primary producers at large spatial scales. Indices of demersal (extent of macroalgae relative to other vegetation, total shallow water area vegetated) and planktonic (seasonally averaged chlorophyll concentration) primary producer communities were derived at whole‐of‐ecosystem scales in 14 estuaries dispersed across a longitudinal gradient using aerial imaging, underwater videography and in situ monitoring. A model selection framework was used to relate annual nutrient loads (total nitrogen [TN], dissolved inorganic nitrogen [DIN], total phosphorus [TP]), sediment loads (TSS), molar stoichiometric load ratios (TN M : TP M ), and estuary water residence times to the demersal and planktonic indices. Dissolved inorganic nitrogen was the best predictor of the extent of macroalgae, total vegetation coverage, and the concentration of planktonic chlorophyll. Rapid increases in all three indices occurred at inorganic nitrogen loads of ∼ 5–10 Mg km −2 yr −1 . There was some evidence that TN M : TP M , TP and TSS loads were informative model covariates. Relative to DIN loads, TP loads were a poor predictor of the macroalgal and planktonic indices. These findings underscore the critical role of catchment‐derived nitrogen in contributing to producer communities at the whole‐of‐ecosystem scale and support the growing consensus that nitrogen loads (in addition to phosphorus) must be managed to effectively alleviate eutrophication in estuaries.

Irrigation as an historical climate forcing - Benjamin I. Cook; Sonali P. Shukla; Michael J. Puma; Larissa S. Nazarenko (Climate Dynamics, 2015)

Sex differences in ventricular–vascular coupling following endurance training - A. D. Lane; H. Yan; S. M. Ranadive; R. M. Kappus; P. Sun; M. D. Cook; I. Harvey; J. Woods; K. Wilund; B. Fernhall (European Journal of Applied Physiology, 2014)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

The response of the South Asian Summer Monsoon circulation to intensified irrigation in global climate model simulations - Sonali P. Shukla; Michael J. Puma; Benjamin I. Cook (Climate Dynamics, 2014)

Effect of cryotherapy on muscle recovery and inflammation following a bout of damaging exercise - Naomi J. Crystal; David H. Townson; Summer B. Cook; Dain P. LaRoche (European Journal of Applied Physiology, 2013)

On the influence of tree size on the climate–growth relationship of New Zealand kauri (Agathis australis): insights from annual, monthly and daily growth patterns - Jan Wunder; Anthony M. Fowler; Edward R. Cook; Maryann Pirie; Shane P. J. McCloskey (Trees, 2013)

Linking anti‐predator behaviour to prey demography reveals limited risk effects of an actively hunting large carnivore - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; Michael D. Jimenez; Rachel C. Cook; John G. Cook; Shannon E. Albeke; Hall Sawyer; P. J. White (Ecology Letters, 2013)
Ecological theory predicts that the diffuse risk cues generated by wide‐ranging, active predators should induce prey behavioural responses but not major, population‐ or community‐level consequences. We evaluated the non‐consumptive effects ( NCE s) of an active predator, the grey wolf ( Canis lupus ), by simultaneously tracking wolves and the behaviour, body fat, and pregnancy of elk ( Cervus elaphus ), their primary prey in the Greater Yellowstone Ecosystem. When wolves approached within 1 km, elk increased their rates of movement, displacement and vigilance. Even in high‐risk areas, however, these encounters occurred only once every 9 days. Ultimately, despite 20‐fold variation in the frequency of encounters between wolves and individual elk, the risk of predation was not associated with elk body fat or pregnancy. Our findings suggest that the ecological consequences of actively hunting large carnivores, such as the wolf, are more likely transmitted by consumptive effects on prey survival than NCE s on prey behaviour.

A strong regional temperature signal in low‐elevation Huon pine - K. J. ALLEN; D. M. DREW; G. M. DOWNES; R. EVANS; E. R. COOK; M. BATTAGLIA; P. J. BAKER (Journal of Quaternary Science, 2013)
We have produced the first annually resolved, centennial‐length tree‐ring chronologies, based on tracheid radial diameter (TRD) and microfibril angle for south‐eastern Australia (SEA) from what would commonly be considered a dendroclimatically suboptimal site. The chronologies exhibit a strong regional temperature signal for the austral summer (nominally November–April) that extends across much of SEA. The strength and spatial extent of the temperature–TRD correlations surpass those between the iconic Tasmanian Mt Read ring‐width chronology and austral summer temperatures, and are more time‐stable. We demonstrate that the value of wood property chronologies for their ability to improve the both the quality and the quantity of highly climate‐sensitive series available for regional annual‐resolution climate reconstructions, in data‐sparse regions in Australasia and beyond, should be examined. In light of the ‘divergence debate’, the time‐stability of relationships with climate, relative to other tree‐ring proxies, also requires further investigation.

A comparison of culture-dependent and culture-independent techniques used to characterize bacterial communities on healthy and white plague-diseased corals of the Montastraea annularis species complex - G. M. Cook; J. P. Rothenberger; M. Sikaroodi; P. M. Gillevet; E. C. Peters; R. B. Jonas (Coral Reefs, 2013)

Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments - B. J. Butterfield; L. A. Cavieres; R. M. Callaway; B. J. Cook; Z. Kikvidze; C. J. Lortie; R. Michalet; F. I. Pugnaire; C. Schöb; S. Xiao; B. Zaitchek; F. Anthelme; et al. (Ecology Letters, 2013)
Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.

Introduction - P. J. Cook (Australian Journal of Earth Sciences, 2013)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

The potential to reconstruct broadscale climate indices associated with southeast Australian droughts from Athrotaxis species, Tasmania - K. J. Allen; J. Ogden; B. M. Buckley; E. R. Cook; P. J. Baker (Climate Dynamics, 2011)

Transcriptome sequencing of an ecologically important graminivorous sawfly: a resource for marker development - N. Cook; N. Aziz; P. E. Hedley; J. Morris; L. Milne; A. J. Karley; S. F. Hubbard; J. R. Russell (Conservation Genetics Resources, 2011)

The Importance of Termites to the CH4 Balance of a Tropical Savanna Woodland of Northern Australia - Hiz Jamali; Stephen J. Livesley; Samantha P. Grover; Tracy Z. Dawes; Lindsay B. Hutley; Garry D. Cook; Stefan K. Arndt (Ecosystems, 2011)

Biogeography of the Australian monsoon tropics - D. M. J. S. Bowman; G. K. Brown; M. F. Braby; J. R. Brown; L. G. Cook; M. D. Crisp; F. Ford; S. Haberle; J. Hughes; Y. Isagi; L. Joseph; J. McBride; et al. (Journal of Biogeography, 2010)
Aim This paper reviews the biogeography of the Australian monsoon tropical biome to highlight general patterns in the distribution of a range of organisms and their environmental correlates and evolutionary history, as well as to identify knowledge gaps. Location Northern Australia, Australian Monsoon Tropics (AMT). The AMT is defined by areas that receive more than 85% of rainfall between November and April. Methods Literature is summarized, including the origin of the monsoon climate, present‐day environment, biota and habitat types, and phylogenetic and geographical relationships of selected organisms. Results Some species are widespread throughout the AMT while others are narrow‐range endemics. Such contrasting distributions correspond to present‐day climates, hydrologies (particularly floodplains), geological features (such as sandstone plateaux), fire regimes, and vegetation types (ranging from rain forest to savanna). Biogeographical and phylogenetic studies of terrestrial plants (e.g. eucalypts) and animals (vertebrates and invertebrates) suggest that distinct bioregions within the AMT reflect the aggregated effects of landscape and environmental history, although more research is required to determine and refine the boundaries of biogeographical zones within the AMT. Phylogenetic analyses of aquatic organisms (fishes and prawns) suggest histories of associations with drainage systems, dispersal barriers, links to New Guinea, and the existence of Lake Carpentaria, now submerged by the Gulf of Carpentaria. Complex adaptations to the landscape and climate in the AMT are illustrated by a number of species. Main conclusions The Australian monsoon is a component of a single global climate system, characterized by a dominant equator‐spanning Hadley cell. Evidence of hot, seasonally moist climates dates back to the Late Eocene, implying that certain endemic elements of the AMT biota have a long history. Vicariant differentiation is inferred to have separated the Kimberley and Arnhem Land bioregions from Cape York Peninsula/northern Queensland. Such older patterns are overlaid by younger events, including dispersal from Southeast Asia, and range expansions and contractions. Future palaeoecological and phylogenetic investigations will illuminate the evolution of the AMT biome. Understanding the biogeography of the AMT is essential to provide a framework for ecological studies and the sustainable development of the region.

Textural variation in the pyrite-rich ore deposits of the Røros district, Trondheim Region, Norway: implications for pyrite deformation mechanisms - Craig D. Barrie; Nigel J. Cook; Alan P. Boyle (Mineralium Deposita, 2010)

Convergence of tree water use within an arid-zone woodland - A. P. O’Grady; P. G. Cook; D. Eamus; A. Duguid; J. D. H. Wischusen; T. Fass; D. Worldege (Oecologia, 2009)

Electronic tags reveal behaviour of captured and discarded fish - F. C. Neat; M. Breen; R. M. Cook; I. M. Gibb; P. J. Wright (Journal of Fish Biology, 2009)
Internally implanted data storage tags (DST) recording hydrostatic pressure (depth) and temperature in Atlantic cod Gadus morhua were used to track the behaviour of nine individuals during fishing operations. Gadus morhua showed identifiable and characteristic behavioural responses to different capture processes. In a unique observation, one fish survived being discarded and upon return to the seabed exhibited a cessation of activity comparable to observations on stressed fish under laboratory conditions.

Resolving relationships in some African fungus-growing termites (Termitidae, Macrotermitinae) using molecular phylogeny, morphology, and field parameters - J. P. E. C. Darlington; R. B. Benson; C. E. Cook; G. Walker (Insectes Sociaux, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Neurobehavioral mutants identified in an ENU-mutagenesis project - Melloni N. Cook; Jonathan P. Dunning; Ronald G. Wiley; Elissa J. Chesler; Dabney K. Johnson; Darla R. Miller; Dan Goldowitz (Mammalian Genome, 2007)

Behavioural and chemical ecology underlying the success of turnip rape (Brassica rapa) trap crops in protecting oilseed rape (Brassica napus) from the pollen beetle (Meligethes aeneus) - S. M. Cook; H. B. Rasmussen; M. A. Birkett; D. A. Murray; B. J. Pye; N. P. Watts; I. H. Williams (Arthropod-Plant Interactions, 2007)

The effect of polymorphism at the serotonin transporter gene on decision-making, memory and executive function in ecstasy users and controls - Jonathan P. Roiser; Robert D. Rogers; Lynnette J. Cook; Barbara J. Sahakian (Psychopharmacology, 2006)

Populations of Myriophyllum alterniflorum L. as bioindicators of pollution in acidic to neutral rivers in the Limousin region - P. Chatenet; D. Froissard; J. Cook-Moreau; P. Hourdin; A. Ghestem; M Botineau; J. Haury (Hydrobiologia, 2006)

Preface – Special Issue: Telluride and selenide minerals in gold deposits – how and why? - C. L. Ciobanu; N. J. Cook; P. G. Spry (Mineralogy and Petrology, 2006)

Rapid development of polyclonal antisera against infectious salmon anaemia virus and its optimization and application as a diagnostic tool - S J McBeath; L M Ellis; P F Cook; L Wilson; K L Urquhart; I R Bricknell (Journal of Fish Diseases, 2006)
Infectious salmon anaemia is an important disease of Atlantic salmon. One of the current methods of diagnosis is the indirect fluorescent antibody test (IFAT), using a monoclonal antibody specific to the haemagglutinin of the virus. The conformationally dependent nature of this antibody could be a drawback in its usefulness in other tests. This study describes the development and optimization of a polyclonal antiserum against infectious salmon anaemia virus, including a method of separating virus from cell culture components within culture supernatant. The antiserum was subsequently optimized for use in a variety of immunological diagnostic tests, including IFAT and an alkaline phosphatase‐based immunoassay, and Western blot.

Influence of pasture management (nitrogen and lime addition and insecticide treatment) on soil organisms and pasture root system dynamics in the field - L. A. Dawson; S. J. Grayston; P. J. Murray; R. Cook; A. C. Gange; J. M. Ross; S. M. Pratt; E. I. Duff; A. Treonis (Plant and Soil, 2003)

An Integrated Pharmacodynamic Analysis of Erythropoietin, Reticulocyte, and Hemoglobin Responses in Acute Anemia - P. Veng-Pederson; S. Chapel; P. R. L. Schmidt; N. H. Al-Huniti; R. T. Cook; J. A. Widness (Pharmaceutical Research, 2002)

An alkaline phosphatase‐based method for the detection of infectious salmon anaemia virus (ISAV) in tissue culture and tissue imprints - L Wilson; S J McBeath; K L Adamson; P F Cook; L M Ellis; I R Bricknell (Journal of Fish Diseases, 2002)
Currently, the presence of infectious salmon anaemia virus (ISAV) is often detected in Atlantic salmon by the use of an indirect fluorescent antibody test. This test is limited by the poor stability of fluorescein isothiocyanate which fades after about a week in storage, preventing the development of stained archive material as a reference source. One possible alternative would be the use of immunohistochemical staining methods to detect ISAV. An immunohistochemical method is presented that uses alkaline phosphatase‐conjugated antibodies and Vector ® Red as a substrate, to detect ISAV in kidney imprints. This paper also describes a procedure where Bouin's fluid is used to successfully inhibit endogenous alkaline phosphatase in tissue samples, prior to immunohistochemical processing. This method provides a stable stain that can be read for many weeks after staining or archived for future reference.

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Nitric oxide donors, sodium nitroprusside and S-nitroso-N-acetylpenicillamine, stimulate myoblast proliferation in vitro - J. A. Ulibarri; P. E. Mozdziak; E. Schultz; C. Cook; T. M. Best (In Vitro Cellular & Developmental Biology - Animal, 1999)

Mineralogy and textural relationships among sulphosalts and related minerals in the Bleikvassli Zn-Pb-(Cu) deposit, Nordland, Norway - N. J. Cook; P. G. Spry; F. M. Vokes (Mineralium Deposita, 1998)

Thermobarometry of the Bleikvassli Zn-Pb-(Cu) deposit, Nordland, Norway - J. L. Rosenberg; P. G. Spry; C. E. Jacobson; N. J. Cook; F. M. Vokes (Mineralium Deposita, 1998)

Multiple independent formations of Tragopogon tetraploids (Asteraceae): evidence from RAPD markers - L. M. COOK; P. S. SOLTIS; S. J. BRUNSFELD; D. E. SOLTIS (Molecular Ecology, 1998)
Polyploidy is widely recognized as a significant force leading to the formation of new plant species. Estimates of the number of angiosperm species with polyploid origins are as high as ≈ 50%; however, in spite of this prevalence, many aspects of polyploid evolution remain poorly understood. Recent studies have suggested that recurrent origins of polyploid species are the rule rather than the exception. The present study is one of only a few designed to quantify the number of independent origins of a polyploid species. The two tetraploid species Tragopogon mirus and T . miscellus (Asteraceae) arose within the past 50 years in the Palouse region of eastern Washington and adjacent northern Idaho. Previous work using morphology, cpDNA and rDNA restriction site analyses, allozymes, cytology, and flavonoid chemistry established that T . mirus had arisen at least five times, and T . miscellus at least twice, on the Palouse. To assess the frequency of multiple origins of these species more rigorously, seven populations of T . mirus and three populations of T . miscellus that were indistinguishable based on previous markers were surveyed using random amplified polymorphic DNA (RAPD) markers; populations of the diploid progenitor species from the same sites were also analysed. Each tetraploid population had a unique RAPD marker profile, suggesting that each population surveyed originated independently of the other populations in the region. Only two of the tetraploid populations combined the RAPD marker profiles of the diploid progenitors occurring at the same site. Both polyploid species, whose ranges and numbers have greatly increased since their formation in the early part of the twentieth century, have formed repeatedly on a local geographical scale and during a short time frame. Furthermore, each tetraploid species is spreading not primarily by dispersal of propagules from a single population of origin, but through repeated, independent polyploidization events that recreate the polyploid taxa.

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Paramagnetic relaxation of ferric "oxyhydroxide" in Victorian brown coal and its structural implications - S. Bocquet; J. D. Cashion; P. S. Cook (Physics and Chemistry of Minerals, 1998)

The effect of severe eccentric exercise-induced muscle damage on plasma elastase, glutamine and zinc concentrations - M. Gleeson; N. P. Walsh; A. K. Blannin; P. J. Robson; L. Cook; A. E. Donnelly; S. H. Day (European Journal of Applied Physiology, 1998)

Tree-ring records from New Zealand: long-term context for recent warming trend - R. D. D'Arrigo; E. R. Cook; M. J. Salinger; J. Palmer; P. J. Krusic; B. M. Buckley; R. Villalba (Climate Dynamics, 1998)

The effects of high-intensity intermittent exercise on the plasma concentrations of glutamine and organic acids - N. P. Walsh; A. K. Blannin; A. M. Clark; L. Cook; P. J. Robson; M. Gleeson (European Journal of Applied Physiology, 1998)

Sea-level pressure variability around Antarctica since A.D. 1750 inferred from subantarctic tree-ring records - R. Villalba; E. R. Cook; R. D. D'Arrigo; G. C. Jacoby; P. D. Jones; M. J. Salinger; J. Palmer (Climate Dynamics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Regional differences in the regulation of intracellular sodium and in action potential configuration in rabbit left ventricle - S. J. Cook; J. P. Chamunorwa; M. K. Lancaster; S. C. O'Neill (Pflügers Archiv - European Journal of Physiology, 1997)

Effects of risks of sperm competition on the numbers of eupyrene and apyrene sperm ejaculated by the moth Plodia interpunctella (Lepidoptera: Pyralidae) - P. A. Cook; Matthew J. G. Gage (Behavioral Ecology and Sociobiology, 1995)

Effect of in ovo bursectomy on the course of an infectious bronchitis virus infection in line C White Leghorn chickens - J. K. A. Cook; T. F. Davison; M. B. Huggins; P. McLaughlan (Archives of Virology, 1991)

The effect of different amounts of spindle tuber and leaf roll on yields of Irish potato - E. L. Leclerg; P. M. Lombard; A. H. Eddins; H. T. Cook; J. C. Campbell (American Journal of Potato Research, 1944)

Effect of different amounts of spindle tuber and leaf roll on yields of Irish potatoes - E. L. Leclerg; P. M. Lombard; A. H. Eddins; H. T. Cook; J. C. Campbell (American Journal of Potato Research, 1944)